ON POINTWISE (f, ?)- STATISTICAL CONVERGENCE OF ORDER ? AND STRONG POINTWISE (V, f, ?)- SUMMABILITY OF ORDER ? OF SEQUENCES OF FUZZY MAPPINGS - Et, Mikail; Altin, Yavuz; Colak, Rifat (Univ Nis, 2023)
In this paper, we introduce pointwise (f, lambda)-statistical convergence of order a and strong pointwise (V, f, lambda)-summability of order alpha of sequences of fuzzy mappings. In addition, we examined some inclusion theorems among these concepts.
Keywords: statistical convergence; pointwise summability; fuzzy mappings